Development of dynamic kinetic resolution on large scale for (±)-1-phenylethylamine - Thalén, Lisa K.; Bäckvall, Jan-E. (Beilstein Journal of Organic Chemistry, 2010)
Candida antarctica lipase B (CALB) and racemization catalyst 4 were combined in the dynamic kinetic resolution (DKR) of (±)-1-phenylethylamine (1). Several reaction parameters have been investigated to modify the method for application on multigram scale. A comparison of isopropyl acetate and alkyl methoxyacetates as acyl donors was carried out. It was found that lower catalyst loadings could be used to obtain (R)-2-methoxy-N-(1-phenylethyl)acetamide (3) in good yield and high ee when alkyl methoxyacetates were used as acyl donors compared to when isopropyl acetate was used as the acyl donor. The catalyst loading could be decreased to 1.25 mol % Ru-catalyst 4 and 10 mg CALB per mmol 1 when alkyl methoxyacetates were used as the acyl donor.
Keywords: dynamic kinetic resolution; kinetic resolution; racemization; Shvo; Candida antartica lipase B